Comparison of Blueberry and Dandelion Aqueous Extracts in the Synthesis of Gold and Silver Nanostructures, and Their Applications as Anti‐ Pseudomonas aeruginosa Agent - Dilek Tepe, Hafize; Şeymanur Aktaş, B. S.; Çeter, Talip; Yazgan, İdris (Wiley, 2023)
Abstract We performed a comparative study using aqueous extracts of dandelion flowers and blueberry fruits to synthesize gold‐ (Au) and silver‐ (Ag) nanostructures (NSs). The blueberry extracts gave nanowire and spherical AuNSs upon changing the ratio of the extracts to Au 3+ precursor while altering the ratio for the dandelion extracts resulted in formation of only anisotropic AuNSs. Similar results were obtained during the AgNSs, where the dandelion extracts resulted in formation of quasi‐spherical AgNSs at the tested ratio (extract/AgNO 3 ratio) while altering the ratio for the blueberry extracts resulted in nanorod and nanoplates formation. We argued that this could be from dominancy of a lone compound or a group of compounds and tested this claim by introducing chrysin and amino acid mixtures to the blueberry extracts. Altering the added chrysin amount triggered nanoplate and spherical AuNSs formation while alteration in amino acid mixture content did not change the morphology, and spherical AuNSs were obtained. The antibacterial studies revealed the AgNSs are toxic to Pseudomonas aeruginosa with 8 μg/mL MBC (minimum bactericidal concentration) and 3 μg/mL values for the blueberry and dandelion extracts synthesized AgNSs while penicillin/streptomycin sulfate mixture carrying Dandelion‐AuNSs gave 12‐times lower MBC value in comparison to free penicillin/streptomycin sulfate mixture.